2015
DOI: 10.1016/j.thromres.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Coagulation Markers and 4F-PCC-Mediated Reversal of Rivaroxaban in a Rabbit Model of Acute Bleeding

Abstract: In summary, in a rabbit model of acute bleeding, treatment with 4F-PCC reduced bleeding to control levels following rivaroxaban 150 μg/kg and 300 μg/kg administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…Although a specific antidote for this drug is not currently available, Phase II studies have demonstrated that andexanet alpha effectively reverses the anticoagulant activity of rivaroxaban [12]. On the other hand, several in vitro studies as well as preclinical studies have shown that PCC has the potential to reverse the anticoagulant activity of rivaroxaban [13][14][15][16][17]. In addition, these data have been confirmed in studies performed in healthy volunteers [18,19].…”
Section: Discussionmentioning
confidence: 98%
“…Although a specific antidote for this drug is not currently available, Phase II studies have demonstrated that andexanet alpha effectively reverses the anticoagulant activity of rivaroxaban [12]. On the other hand, several in vitro studies as well as preclinical studies have shown that PCC has the potential to reverse the anticoagulant activity of rivaroxaban [13][14][15][16][17]. In addition, these data have been confirmed in studies performed in healthy volunteers [18,19].…”
Section: Discussionmentioning
confidence: 98%
“…Valuable insights have also been gained from studies using other standardized injuries in small animals, including kidney incision, hepatosplenic bleeding, and mesenteric bleeding (57, 58, 61, 62, 64). Results from these models are broadly consistent, though it is important to be aware of the distinctions between individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…The action of 4F-PCC as a rivaroxaban reversal agent has also been demonstrated in rabbits (57, 58). While 4F-PCC (Kaskadil 40 U/mL or Beriplex 25 U/kg, 50 U/kg, or 100 U/kg) did not reduce the increase in bleeding seen with administration of rivaroxaban 5 mg/kg or 450 μg/kg in hepatosplenic and kidney incision bleeding models, Beriplex dose-dependently reduced blood loss and bleeding time at lower rivaroxaban doses in the kidney incision model.…”
Section: Reversal Of Rivaroxabanmentioning
confidence: 95%
See 1 more Smart Citation
“…FVIIa effectively reduced rivaroxabaninduced bleeding time but not blood loss in a rabbit model [ 15 ]. Four-factor PCC has been shown to be effective in reducing bleeding following liver laceration in dabigatran-treated animals and following kidney laceration in rivaroxabantreated animals [ 16 ]. Animal studies have also pointed out that stoppage of bleeding following administration of PCC or rFVIIa did not necessarily correlate with a complete reversal of plasma clotting time prolongation.…”
Section: Animal Studiesmentioning
confidence: 99%